Effect of metakaolin on mechanical properties of different grades concretes inclusion of recycled aggregates from C& D waste and ceramic waste. - N. patel, Vimalkumar; D. Modhera, C; M. chavda, Mehul; M. Panseriya, Maulik (International Journal of Engineering and Technology, 2018)
As concrete is the second highest utilized material after water in the world, the improvement in the performances of concrete is the requirement of todayâ€™s era. In addition, the use of mineral admixture like Metakaolin helps to achieve good performance of concrete even prepared by utilizing recycled construction and demolition (C&D) waste aggregate and recycled ceramic waste aggregate. In present study Ordinary Portland cement has been partially replaced by Metakaolin in different grades selected recycled aggregate concrete(RAC) and recycled ceramic waste aggregate concrete(CAC). The deficiencies in different mechanical properties of these selected concretes with respect to reference concretes has been observed experimentally and there were retained by replacing cement with Metakaolin(MK) about 7.5% by weight of cement.Â